2018
DOI: 10.5935/abc.20180037
|View full text |Cite
|
Sign up to set email alerts
|

Infection in Patients with Decompensated Heart Failure: In-Hospital Mortality and Outcome

Abstract: BackgroundHeart failure (HF) is a syndrome, whose advanced forms have a poor prognosis, which is aggravated by the presence of comorbidities.ObjectiveWe assessed the impact of infection in patients with decompensated HF admitted to a tertiary university-affiliated hospital in the city of São Paulo.MethodsThis study assessed 260 patients consecutively admitted to our unit because of decompensated HF. The presence of infection and other morbidities was assessed, as were in-hospital mortality and outcome after di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 6 publications
2
16
0
Order By: Relevance
“… 16 Cardoso et al. 17 reported that the mortality rate in patients with infection and cardiac insufficiency was higher than that in patients with infection alone (21.5% vs 17.6%, P < 0.05). Therefore, patients with sepsis and pulmonary infection may also have pulmonary hypertension, which increases the cardiac load and aggravates myocardial injury, thus leading to a higher risk of death.…”
Section: Discussionmentioning
confidence: 97%
“… 16 Cardoso et al. 17 reported that the mortality rate in patients with infection and cardiac insufficiency was higher than that in patients with infection alone (21.5% vs 17.6%, P < 0.05). Therefore, patients with sepsis and pulmonary infection may also have pulmonary hypertension, which increases the cardiac load and aggravates myocardial injury, thus leading to a higher risk of death.…”
Section: Discussionmentioning
confidence: 97%
“…Prescriptions of amoxicillin and clavulanic acid can serve as proxy for the underlying infection. Infections were reported to be common precipitating factors for HF decompensation requiring hospital admission, especially with respiratory infection being common [12,13,15,16]. Accordingly, our study found a significantly increased risk for hospitalization after amoxicillin/ clavulanic acid prescription (OR 3.25, 15 days).…”
Section: Amoxicillin/clavulanic Acidmentioning
confidence: 47%
“…While medications themselves may be risk factors for decompensation or development of HF, they can also serve as proxies for acute conditions presenting potential risk factors. Conditions such as arrhythmia, worsening renal function, and infections [12,13] are common complications in patients suffering from HF and were described to be precipitating factors for HF hospitalization [3,[14][15][16][17][18]. Additionally, electrolyte imbalances appear frequently in HF patients [19][20][21][22], especially as several drugs commonly used in heart failure treatment may lead to hypo-or hyperkalemia, respectively [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…As it is known, pulmonary infection is one of the risk factors for higher mortality rates in acute HF patients in the treatment. 11 But this patient's data does not include patients who died because we did not measure the mortality rate in this study.…”
Section: Discussionmentioning
confidence: 99%